Population-based Survey of Invasive Bacterial Diseases, Greenland, 1995–2004 - Meyer, Annette; Ladefoged, Karin; Poulsen, Peter; Koch, Anders
Invasive bacterial disease occurs frequently among native populations in the Arctic. Although a variety of bacteria are involved in invasive bacterial disease in Greenland, Streptococcus pneumoniae, Escherichia coli, Staphylococcus aureus, and other staphylococci are responsible for most cases (69%); incidence varies according to region and ethnicity.